Adrenal Hemangioma: A Case of Retroperitoneal Tumor - Genta Iwamoto; Kota Shimokihara; Takashi Kawahara; Daiji Takamoto; Masahiro Yao; Jun-ichi Teranishi; Masako Otani; Hiroji Uemura (Case Reports in Medicine)
Introduction. Adrenal hemangioma is a rare disease, with only some 60 cases reported previously. Due to the difficulty of the preoperative diagnosis of adrenal hemangioma, almost all of the cases were diagnosed by a histopathological analysis of surgical specimens. Case Presentation. A 52-year-old man was referred to our department for further examination of his left retroperitoneal tumor. He had received hemodialysis due to chronic renal failure resulting from membranous nephropathy. Computed tomography revealed a mass around his left hilum. Magnetic resonance imaging (MRI) and positron-emission tomography (PET)-CT were unable to confirm or deny malignancy, and tumor markers, including CEA and CA19-9, showed slight elevation. His tumor grew from 38 mm to 54 mm in diameter in 7 months of follow-up. We therefore planned retroperitoneal tumor resection with left nephrectomy. Histopathologically, hyperplastic small vessels with hemorrhaging and denaturation were seen. The endothelial cells showed no variants or division of the nucleus. Based on this diagnosis, no further therapy was performed. He has had no recurrence in the eight months since the surgery. Conclusion. We herein report a rare case of adrenal hemangioma.